Influence of Coronavirus on Consumer Behaviour in the Ecological Context - Andrea Seberíni (Studia Ecologiae et Bioethicae)
The COVID-19 pandemic has fundamentally changed the world as we know it. People are living differently, buying differently and in many ways, thinking differently. This study takes the lead of research by trying to answer the following research question:  How does the coronavirus impact consumer behaviour in the ecological context? The paper begins with a presentation of the concept of consumer behaviour, its theoretical background and definition, and then discusses the question of the pandemic and its socio – economic effects on the consumer. Next, the paper presents a study on consumer behaviour in the era of the pandemic. Finally, it analyses the impact of consumer behaviour in the era of the pandemic on the environment.